Pengaruh Dimensi Kualitas Pelayanan PT. Astra International, Tbk – Daihatsu, Malang Terhadap Kepuasan Pelanggan. - Nalendra, Ega Fadin; Pinando, Sugeng (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research was based on some problems about the service quality that PT. Astra International, Tbk – Daihatsu, Malang gives to their customer which needs to be fixed and improved. The problems found in their service quality indicates that they need to find a way to maintaining a good service quality for their loyal customers. This research’s goal is to analyze and knowing the influence from the dimentionof service quality simultaneously and partially and to prove that assurance is the variable that have the dominant influence amongs service quality dimention agains the customer satisfaction.Thispopulation’sresearch is the customer that uses the official garage to servicing their cars for September - November 2012period  with the amount of 155 people and the amount of sample in this research is 112 respondent. An analytical method in this research is multiple regression analysis. Based on this research findings it is found that all of five service quality dimentions is simultaneously affects the customer satisfaction, but partially only three of the five service quality dimention (reliability, responsiveness, and assurance) thataffects the customer satisfaction significantly. Assurance is the dominant variable that affects the customer satisfaction. Some suggestion that researcher can give are: to create a good customer satisfaction the company should create a positive synergy amongs the five service quality dimentions. Tangibility and emphaty did not have a significant effect to customer satisfaction, thus the company just need to maintain this two variables according to their existing standard. To improve the customer knowledge about the benefit of using the booking service facilities is with sales promotion for those who uses the booking service facility. Keywords: Influence, Service Quality, Customer Satisfaction